Another reason : science and the imagination of modern India - Prakash, Gyan, 1952- (Book collections on Project MUSE., 1999)
"Another Reason is a bold and innovative study of the intimate relationship between science, colonialism, and the modern nation. Gyan Prakash, one of the most influential historians of India writing today, explores in fresh and unexpected ways the complexities, contradictions, and profound importance of this relationship in the history of the subcontinent. He reveals how science served simultaneously as an instrument of empire and as a symbol of liberty, progress, and universal reason - and how, in playing these dramatically different roles, it was crucial to the emergence of the modern nation." "Throughout, Prakash draws on major and minor figures on both sides of the colonial divide, including Mahatma Gandhi, Jawaharlal Nehru, the nationalist historian and novelist Romesh Chunder Dutt, Prafulla Chandra Ray (author of A History of Hindu Chemistry), Rudyard Kipling, Lord Dalhousie, and John Stuart Mill."--Jacket.